2018
DOI: 10.17269/s41997-018-0101-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of socio-demographic factors on mental health and addiction high-cost use: a retrospective, population-based study in Saskatchewan

Abstract: ObjectiveA small proportion of the population accounts for the majority of healthcare costs. Mental health and addiction (MHA) patients are consistently high-cost. We aimed to delineate factors amenable to public health action that may reduce high-cost use among a cohort of MHA clients in Saskatoon, Saskatchewan.MethodsWe conducted a population-based retrospective cohort study. Administrative health data from fiscal years (FY) 2009–2015, linked at the individual level, were analyzed (n = 129,932). The outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Our estimates of total health care costs were lower than those reported in another recent study for Ontario, for which data were available from all health care settings. 1 This was most apparent for the highest-cost users, who have been shown by prior research to be heavier-than-average users of non-acute hospital care, continuing care services and mental health care, 1,17 the settings that were not available for our study. The top 1% of highcost users in the prior study had expenditures exceeding $44 906 in fiscal year 2011/12, which was more than double our result of $22 254 in fiscal year 2016/17, even without accounting for inflation.…”
Section: Limitationsmentioning
confidence: 84%
“…Our estimates of total health care costs were lower than those reported in another recent study for Ontario, for which data were available from all health care settings. 1 This was most apparent for the highest-cost users, who have been shown by prior research to be heavier-than-average users of non-acute hospital care, continuing care services and mental health care, 1,17 the settings that were not available for our study. The top 1% of highcost users in the prior study had expenditures exceeding $44 906 in fiscal year 2011/12, which was more than double our result of $22 254 in fiscal year 2016/17, even without accounting for inflation.…”
Section: Limitationsmentioning
confidence: 84%
“…Measures of socio-economic status (SES), such as, unstable housing, and food insecurity, have previously been found to be associated with high-cost health care use, [4, 22, 28, 30], To the best of our knowledge this is the first population-based study to define high-cost users within their health profile group and consider SES in regression models. We hypothesize this method provides better specificity to understanding high-cost users of health care services.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent use of inpatient mental health care may be attributable to the underlying lack of access to outpatient care [ 5 ] and substandard hospital care [ 6 , 7 ]. For example, a recent study conducted in Canada reported that having a good connection to a primary care provider decreased the probability of being a high-cost health service user [ 8 ]. Inpatient hospitalizations for patients with psychiatric disorders were reported that depend on the type of illness; that is, inpatient readmission is common for individuals with severe mental illness (e.g., schizophrenia, mood disorders, bipolar disorder and psychoses) [ 9 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carriere et al [ 18 ] found that hospitalization rates for mental illness were higher for Aboriginals living on and off reserve, Metis, and Inuit than for the non-Aboriginal population, regardless of disease category. Females were found to have higher use of health facilities for psychiatric illness than males [ 8 ]. Geographical characteristics such as population density, place of residence and proximity to service have been identified as important factors in several studies.…”
Section: Introductionmentioning
confidence: 99%